2023
DOI: 10.1021/acs.jcim.3c00778
|View full text |Cite
|
Sign up to set email alerts
|

Markov State Models and Perturbation-Based Approaches Reveal Distinct Dynamic Signatures and Hidden Allosteric Pockets in the Emerging SARS-Cov-2 Spike Omicron Variant Complexes with the Host Receptor: The Interplay of Dynamics and Convergent Evolution Modulates Allostery and Functional Mechanisms

Sian Xiao,
Mohammed Alshahrani,
Grace Gupta
et al.

Abstract: The new generation of SARS-CoV-2 Omicron variants displayed a significant growth advantage and increased viral fitness by acquiring convergent mutations, suggesting that the immune pressure can promote convergent evolution leading to the sudden acceleration of SARS-CoV-2 evolution. In the current study, we combined structural modeling, microsecond molecular dynamics simulations, and Markov state models to characterize conformational landscapes and identify specific dynamic signatures of the SARS-CoV-2 spike co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 143 publications
3
29
0
Order By: Relevance
“…Our previous studies showed that well-ordered and stable "hook-like" conformation of the RBM tip is maintained in BA.2 and XBB.1.5 variants due to hydrophobic interactions provided by F486 (BA.2) and F486P (XBB.1.5). 70,71 The RMSF analysis of the ACE2 residues showed similar profiles across all the examined variants (Supporting Information, Figure S7). The The conformational ensembles of the S-RBD complexes with ACE2 were subjected to distance fluctuation stability analysis based on the dynamic residue correlations (Figure 6B).…”
Section: Atomistic MD Simulations Reveal Variant-specific Signatures ...mentioning
confidence: 76%
See 4 more Smart Citations
“…Our previous studies showed that well-ordered and stable "hook-like" conformation of the RBM tip is maintained in BA.2 and XBB.1.5 variants due to hydrophobic interactions provided by F486 (BA.2) and F486P (XBB.1.5). 70,71 The RMSF analysis of the ACE2 residues showed similar profiles across all the examined variants (Supporting Information, Figure S7). The The conformational ensembles of the S-RBD complexes with ACE2 were subjected to distance fluctuation stability analysis based on the dynamic residue correlations (Figure 6B).…”
Section: Atomistic MD Simulations Reveal Variant-specific Signatures ...mentioning
confidence: 76%
“…The advantages of this approach are fast and accurate predictions of the effect of mutations on both the strength of the binding interactions and on the stability of the complex using statistical potentials and neural networks. The benchmark studies and our analysis of different approaches for assessment of mutational effects on the S-RBD binding showed that the BeatMusic approach is comparable to other knowledge-based structural methods such as D-complex, physics-based FoldX potentials, , and BindProfX approach . The recent analysis of computational tools for estimating protein–protein binding showed that physics-based FoldX methods often display a similar predictive power to comparable but much faster knowledge-based methods such as BeatMusic which is indispensable for massive mutational scanning experiments .…”
Section: Methodsmentioning
confidence: 87%
See 3 more Smart Citations